To simplify the expression \( \frac{1}{2}(z+4) - 3\left(\frac{1}{4}z + 1\right) \), follow these steps:
- Distribute \( \frac{1}{2} \) and \( -3 \):
\[ \frac{1}{2}(z+4) = \frac{1}{2}z + \frac{1}{2} \cdot 4 = \frac{1}{2}z + 2 \]
\[ -3\left(\frac{1}{4}z + 1\right) = -3 \cdot \frac{1}{4}z - 3 \cdot 1 = -\frac{3}{4}z - 3 \]
- Combine the two parts:
\[ \left(\frac{1}{2}z + 2\right) + \left(-\frac{3}{4}z - 3\right) \]
- Combine the \( z \) terms and the constant terms:
\[ \frac{1}{2}z - \frac{3}{4}z + 2 - 3 \]
- To combine the \( z \) terms, we need a common denominator. The common denominator for \( \frac{1}{2} \) and \( -\frac{3}{4} \) is \( 4 \):
\[ \frac{1}{2} = \frac{2}{4} \]
Thus,
\[ \frac{2}{4}z - \frac{3}{4}z = \left(\frac{2 - 3}{4}\right)z = -\frac{1}{4}z \]
- Combine the constant terms:
\[ 2 - 3 = -1 \]
- So the final expression is:
\[ -\frac{1}{4}z - 1 \]
Thus, the final result is
\[ -\frac{1}{4}z - 1 \]